Manipulation of Metabolic Pathways to Develop Vitamin-Enriched Crops for Human Health - Jiang, Ling; Wang, Weixuan; Lian, Tong; Zhang, Chunyi (Frontiers in Plant Science, 2017)
Summary Vitamin deficiencies are major forms of micronutrient deficiencies, and are associated with huge economic losses as well as severe physical and intellectual damages to humans. Much evidence has demonstrated that biofortification plays an important role in combating vitamin deficiencies due to its economical and effective delivery of nutrients to populations in need. Biofortification enables food plants to be enriched with vitamins through conventional breeding and/or biotechnology. Here, we focus on the progress in the manipulation of the vitamin metabolism, an essential part of biofortification, by the genetic modification or by the marker-assisted selection to understand mechanisms underlying metabolic improvement in food plants. We also propose to integrate new breeding technologies with metabolic pathway modification to facilitate biofortification in food plants and, thereby, to benefit human health.